Прогноз розвитку фондового ринку України в умовах економічної нестабільності - Бачо Роберт; Robert Bacho; Bacsó Róbert; Пойда-Носик Ніна; Poyda-Nosyk Nina; Pojda-Noszik Nina; Макарович Вікторія; Vyktorya Makarovych; Makarovics Viktória; Ганусич Вероніка; Veronika Hanusych; Hanuszics Veronika; et al. (Видавничий дім «Гельветика», 2025)
Резюме. У статті досліджено особливості розвитку фондового ринку України в умовах економічної нестабільності з акцентом на адаптивність інституційної структури та ефективність регуляторних механізмів. Акцентовано увагу на важливості фондового ринку як ключового елемента фінансової системи, що забезпечує перерозподіл капіталу, мобілізацію інвестиційних ресурсів та формування індикативних сигналів для прийняття стратегічних рішень. За результатами дослідження здійснено кореляційно-регресійний аналіз взаємозв’язку між рівнем проникності фондового ринку та макро- і мікроекономічними чинниками. Побудована в рамках дослідження регресійна модель дозволила здійснити кількісний прогноз рівня проникності фондового ринку до 2027 року, який демонструє поступове зростання ринкової активності, хоча й зберігаються інституційні бар'єри та структурні диспропорції. Отримані результати сприяють розумінню функціональних взаємозв’язків між фондовим ринком та динамікою економічних показників країни, а також дозволяють окреслити основні напрями державної політики у сфері фінансового ринку.

Abstract. The article explores the peculiarities of the development of Ukraine's stock market under conditions of economic instability, with an emphasis on the adaptability of the institutional structure and the effectiveness of regulatory mechanisms. Particular attention is given to the significance of the stock market as a key component of the financial system, ensuring the redistribution of capital, the mobilisation of investment resources, and the formation of indicative signals for strategic decision-making. The aim of the study is to identify the key factors influencing the penetration level of Ukraine's stock market, as well as to develop a quantitative forecasting model for the stock market's development in the context of structural economic transforma-tion. The research employs a comprehensive set of economic and statistical analysis methods, including correlation-regression analysis and economic forecasting techniques. The results of the research indicate that the dynamics of the stock market over the period 2019–2024 follow a wave-like trajectory, characterised by sharp declines under the influence of crisis factors and a slow recovery in the post-crisis period. The article conducts a correlation-regression analysis of the interrelationship between the penetration level of the stock market and macro- and microeconomic factors. It is established that the primary determinant of market activity is the trading volume, which shows the strongest positive correlation with the market penetration indicator. Conversely, GDP, the number of collective investment institutions, and the PFTS index exhibit inverse or weak correlations, highlighting the low integration of the stock market into the overall economic dynamics and the necessity to revitalise the corporate sector. The regression model developed within the research framework enabled a quantitative forecast of the stock market's penetration level up to the year 2027, demonstrating a gradual increase in market activity, although institutional barriers and structural imbalances persist. The findings contribute to a deeper understanding of the functional interconnections between the stock market and the dynamics of the country's economic indicators, and allow for the delineation of key directions of state policy in the field of the financial market.
Projection of the Ukrainian stock market development amid economic instability
Весь випуск: https://economdevelopment.in.ua/index.php/journal/issue/view/36
Keywords: фондовий ринок; ринок капіталу; економічна нестабільність; інвестиційна активність; прогнозування